Implementation Cryptography and Access Control on IoT-Based Warehouse Inventory Management System - Muhammad Yusuf; Arizal Arizal; Ira Rosianal Hikmah (MATRIK : Jurnal Manajemen, Teknik Informatika dan Rekayasa Komputer, 2022)
Warehousing is a product storage management activity to ensure product availability, so inventory management is needed to oversee the movement of logistics and equipment. Some things need to be considered in the storage process, such as the suitability of the storage location, safe from theft, and safe from physical disturbances. Vulnerabilities can occur when unauthorized users find out information from the database regarding stored goods, so a security mechanism for the warehouse database is needed. In addition, proper identification needs to be made of someone trying to access the database. In this research, a Warehouse Inventory Management System (WIMS) was created by implementing the AES-128 cryptographic algorithm, which was built using ESP32 and Raspberry Pi 3 devices. Time Password (T-OTP). The results show that the built system can overcome inventory problems in conventional warehousing management systems and implement data security using the AES-128 algorithm. The application of two-factor authentication in the form of smartcards and T-OTP shows very good results in testing its accuracy to overcome the vulnerability of unauthorized access to the system database